The complete chloroplast genome sequence of the Cucurbita ficifolia Bouché (Cucurbitaceae). Issue 11 (2nd November 2021) - Cong, Zhou; Cai, Lijuan; Zhang, Yu; Su, Wenzhen; Li, Huiying; Zhu, Qianglong
Abstract: Cucurbita ficifolia Bouché is an important germplasm resource used for rootstock and hypoglycemic food in Cucurbitaceae. The complete chloroplast genome sequence of C. ficifolia has been determined in this study. The total genome size is 157, 533 bp in length and contains a pair of inverted repeats (IRs) of 25, 639 bp, which were separated by large single copy (LSC) and small single copy (SSC) of 88, 112 bp and 18, 143 bp, respectively. A total of 130 genes were predicted including 86 protein-coding genes, eight rRNA genes and 36 tRNA genes. Further, Maximum-likelihood phylogenetic analysis revealed that C. ficifolia is a base clade of genus Cucurbita and closer to Cucurbita maxima. The chloroplast genome of C. ficifolia would promote the germplasm exploration, phylogenetic relationships, and molecular biology researches in Cucurbita.